Case Report: Non-traumatic Unilateral Forelimb Arterial Thrombosis Associated With Hyperadrenocorticism in a Dog - Eom, Tae-Yoon; Choi, Ju-Won; Yoon, Kyong-Ah; Jeong, Soon-Wuk; Kim, Jung-Hyun (Frontiers in Veterinary Science, 2021)
A 16-year-old spayed female Pomeranian dog presented with acute onset of pain and non-weight-bearing lameness in the right forelimb. Upon arrival at the hospital, knuckling, coolness, pain, and cyanosis was seen in the affected forelimb. Peripheral blood glucose concentration and body surface temperature differed between the right and left forelimbs. Hypercoagulable thromboelastographic results and increased D-dimer levels were suggestive of thrombus. Accordingly, recombinant tissue plasminogen activator (rtPA) was administered intravenously. Prompt clinical improvements (including restored warmth of the affected limb) occurred, and rtPA was discontinued after two shots administered 2 hours apart owing to concerns of bleeding side effects. The dog was discharged 6 days after admission, and outpatient treatment with clopidogrel was continued. Following patient stabilization, further examinations for underlying diseases of hypercoagulability were conducted; hyperadrenocorticism (HAC) was diagnosed, and oral trilostane therapy was thus administered. Eight weeks later, the patient regained normal mobility. This is the first case report of non-traumatic unilateral forelimb arterial thrombosis associated with HAC in a dog. In this patient, normal mobility was regained after initiation of rtPA and clopidogrel, followed by long-term outpatient treatment with trilostane therapy for hyperadrenocorticism.